A clinical and MRI retrospective cohort study of patients with juvenile idiopathic arthritis (JIA) to determine if initial temporomandibular joint (TMJ) examination findings are associated with severity of TMJ arthritis. Issue 4 (April 2022) - Scolozzi, Paolo; Rabufetti, Alessandro; Hanquinet, Sylviane; Hofer, Michaël; Courvoisier, Delphine S.; Antonarakis, Gregory S.
Abstract: The purpose of the present study was to evaluate the association between initial TMJ examination findings and clinical and MRI severity of TMJ arthritis in a cohort of patients with JIA. The clinical variables were signs and symptoms at the initial TMJ evaluation. Outcome was the severity of TMJ arthritis as evaluated clinically by the Helkimo clinical dysfunction indices and by MRI. Associations of signs and symptoms with clinical and MRI severity were analyzed using a Fisher exact test and linear regression. The sample was composed of 101 patients with a mean age of 12.8 years, 76% of which were girls. Subjective difficulty in opening the mouth wide and objective limited MIO were the only clinical findings associated with both the severity of clinical dysfunction (p = 0.001 and p < 0.001, respectively) and the acute (p = 0.008 and p = 0.001, respectively) and chronic (p = 0.006 and p = 0.001, respectively) MRI severity of the TMJ arthritis. The results of this study suggest that in patients with JIA, limited mouth opening at the initial TMJ assessment may be a valid indicator of clinical severity of TMJ arthritis, which correlates with severity as seen on MRI.